A Real Alternative? – How Alternative News Media Coverage Compares to the Mainstream in New Zealand - Acton, Jay (Auckland University of Technology, 2019)
The public receives most of its information about important national and international events through the news media. Since the advent of the internet, mainstream news media has experienced a decline in its audience as the number and popularity of alternative media outlets has dramatically increased. What the mainstream and alternative news media include in their stories and how they frame these stories has implications for citizens and society. This study compares how news is covered by online text-based alternative and mainstream news in New Zealand using quantitative content analysis. Article length, Context Factors, Number, Type, and Balance of Sources, as well as Dominant Media Frames were measured in coverage of 25 news events across four mainstream and four alternative New Zealand news outlets. The research showed that, compared to the alternative news media, the mainstream news was more consistent, and slightly longer in average article length; used approximately 25% more context factors; relied heavily on government sources versus alternative news reliance on expert sources, and used approximately 30% more sources overall; were 30% more ‘balanced’ in their use of sources, and approximately seven times less likely to run a story using an unopposed source. Furthermore, the research showed that the ‘conflict’ frame dominated mainstream media news stories – wherein two or more sides to a story are presented - while the dominant frame in alternative news media stories was that of ‘attribution of responsibility’. While the results of some of the measures – including article length, context factors, and number of sources – proved difficult to interpret, the mainstream media’s more balanced use of sources, reliance on official government sources, and use of the conflict media frames were explainable in that it reflects the appearance of professional journalism’s values of balance and objectivity. The results showing alternative news media’s less balanced use of sources and their predominant attribution of responsibility framing was supported by much of the literature around alternative journalism describing it, in part, as oppositional, justice-seeking, and ‘activist’ journalism. However, while these results highlight some clear differences between the two types of media, it is worth considering the following; that historically, the mainstream news media, in a sense, emerged from what can be considered a proto-alternative oppositional news media; that the two have thereafter functioned in a complex relation to one another; and that with both alternative and increasingly mainstream news media moving to the internet, they may be in a relatively convergent period.
Keywords: Media studies; Alternative media; Propaganda model; News frames